UPAYA PENINGKATAN MINAT BELAJAR MATEMATIKA PADA MATERI PERKALIAN MELALUI MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBASIS MEDIA “BAMBOOZLE” DI KELAS IV SEKOLAH DASAR - Destri Aulia Pratiwi; Sari Efriyani; Rut Putri Rajagukguk; Aulya Herliyana Putri; Destrinelli; Desy Rosmalinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to increase students' interest in learning mathematics, particularly in multiplication, through the implementation of the cooperative learning model Teams Games Tournament (TGT) assisted by Baamboozle media. The background of this research stems from the low learning interest and engagement of students during mathematics lessons, which has negatively impacted their learning outcomes. Monotonous teaching methods and the lack of engaging media have contributed to students' lack of enthusiasm in the classroom.This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of this study were 16 fourth-grade students at SDN 56/I Desa Aro. Data were collected through learning outcome tests and observation sheets to assess student activity. The collected data were analyzed both qualitatively and quantitatively. The results showed that applying the TGT cooperative learning model integrated with Baamboozle media significantly improved students' interest and learning engagement. The percentage of active student participation increased from 47% in the first cycle to 85% in the second cycle. Furthermore, students demonstrated greater enthusiasm, active participation in group discussions, and a better understanding of multiplication concepts. In conclusion, the TGT model assisted by Baamboozle media proved to be effective in enhancing students’ interest in learning mathematics and in creating an enjoyable, interactive, and meaningful learning environment for elementary school students. This approach is recommended as an alternative method to support active learning and improve academic performance in mathematics.